Altered Functional Connectivity of the Salience Network in Problematic Smartphone Users - Ahn, Jaeun; Lee, Deokjong; Namkoong, Kee; Jung, Young-Chul (Frontiers in Psychiatry, 2021)
Smartphone plays an integral role in daily life, providing convenience and increasing efficiency. However, smartphones also cause adverse effects when used excessively. The purpose of this study was to examine the underlying neurobiological alterations that arise from problematic smartphone use. We performed resting state seed-based functional connectivity (FC) analysis of 44 problematic smartphone users and 54 healthy controls. This analysis assessed the salience, central executive, default mode, and affective networks. Compared to controls, problematic smartphone users showed enhanced FC within salience network and between salience and default mode network. On the contrary, we observed decreased FC between salience and central executive network in problematic smartphone users compared to controls. These results imply that problematic smartphone use is associated with aberrant FC in key brain networks. Our results suggest that changes in FC of key networks centered around salience network might be associated with problematic smartphone use.